Examining the Role of Communication and Human Resource Quality in Boosting Employee Performance: A Case Study of the Papua Maritime and Fisheries Office - Lakehu, Anita; Kambuaya, Balthasar; Wanma, Johanis R. (Adhigana Papua: Jurnal Ilmiah Magister Manajemen, 2025)
The objective of this research is to determine the influence of Human Resource (HR) Quality, Communication, and Organizational Commitment on Employee Performance at the Papua Province Maritime and Fisheries Service Office. The population in this research consists of all employees involved at the Papua Province Maritime and Fisheries Service Office. The number of respondents in this research is 93. Data collection was conducted through direct surveys using questionnaires, and Multiple Regression Analysis was used to test the hypotheses in this research. The research findings show that the quality of human resources, communication, and organizational commitment have a partial effect on employee performance. Furthermore, this study proves that simultaneously, the quality of human resources, communication, and organizational commitment have an impact on employee performance at the Office of Marine and Fisheries Department of Papua Province.